2011
DOI: 10.1038/eye.2011.313
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis following open-globe injuries

Abstract: The incidence of traumatic endophthalmitis may be decreasing due to earlier wound closure and prompt initiation of antibiotics. Risk factors for endophthalmitis include retained intraocular foreign body, rural setting of injury, disruption of the crystalline lens, and a delay in primary wound closure. The microbiology in the post-traumatic setting includes a higher frequency of virulent organisms such as Bacillus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
141
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 49 publications
5
141
1
11
Order By: Relevance
“…16 The relatively higher frequency of fungi might be associated with open-globe injuries involving vegetable matter or soil contamination due to the mild and moist climate in our series. 17 There was also a relatively high incidence of B. cereus, which is known to be highly virulent and to cause rapid progression to panophthalmitis, [18][19][20] which might be associated with open-globe injuries with intraocular foreign bodies, particularly metal objects and the variety of trauma causes in our series. To optimize the prevention of endophthalmitis using prophylactic antibiotics, it is imperative to understand which antimicrobial regimen will be effective against the possible causative organisms.…”
Section: Discussionmentioning
confidence: 88%
“…16 The relatively higher frequency of fungi might be associated with open-globe injuries involving vegetable matter or soil contamination due to the mild and moist climate in our series. 17 There was also a relatively high incidence of B. cereus, which is known to be highly virulent and to cause rapid progression to panophthalmitis, [18][19][20] which might be associated with open-globe injuries with intraocular foreign bodies, particularly metal objects and the variety of trauma causes in our series. To optimize the prevention of endophthalmitis using prophylactic antibiotics, it is imperative to understand which antimicrobial regimen will be effective against the possible causative organisms.…”
Section: Discussionmentioning
confidence: 88%
“…[2,18,[20][21][22][23][24] The general consensus is that a delay in IOFB removal increases the risk for endophthalmitis. [24][25][26][27][28][29] In contrast to this view, Colyer and colleagues [30] have reported prompt wound closure and systemic antibiotics followed by delayed removal with no reported endophthalmitis. When we compared the groups that underwent IOFB removal within 48 hours (53%) and IOFB removal after 48 hours (47%) for initial incidence of endophthalmitis, there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Reported rates of endophthalmitis in open globe injury are higher than for intraocular surgery, presumably because of nonsterile conditions at the time of an injury. 1 Rates of posttraumatic endophthalmitis vary; in a review of 558 patients with open globes, Andreoli et al 2 found a rate of 0.9% of endophthalmitis, whereas Verbraeken and Rysselaere 3 found a rate of 4% in 615 patients, Ariyasu et al 4 found a rate of 7.2% in 670 open globe patients, and Essex et al 5 found a rate of 6.8% in 250 patients. The rate of endophthalmitis after intraocular surgery, by comparison, is approximately 0.001%.…”
Section: ' Introductionmentioning
confidence: 95%
“…The rate of endophthalmitis after intraocular surgery, by comparison, is approximately 0.001%. 1 In addition to suffering from higher endophthalmitis rates, patients with posttraumatic endophthalmitis have worse postoperative outcomes than patients with postoperative endophthalmitis. 6 In a study of 25 patients with endophthalmitis, Verbraeken and Rysselaere 3 found only 38% to recover functional vision (light perception or better), compared with 60% of postoperative endophthalmitis patients resulting in functional vision in a previous study by the same author.…”
Section: ' Introductionmentioning
confidence: 99%